2008
DOI: 10.1007/s11886-008-0057-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective site pacing: Rationale and practical application

Abstract: Although it has become traditional to place permanent pacemaker leads at the right ventricular apex and right atrial appendage, pacing from these locations poorly mimics normal physiology. A growing evidence base shows that right ventricular apical pacing results in ventricular dyssynchrony and various adverse effects. Provocative data from early trials suggest that pacing from alternate sites in the right ventricle--His bundle pacing, para-Hisian pacing, septal right ventricular outflow tract pacing, and righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 64 publications
0
7
0
3
Order By: Relevance
“…Because several studies have demonstrated an association between RVA pacing and an increased risk of heart failure or LV dysfunction, 17–20 alternative pacing sites have been investigated intensively 6,21 . RVOT pacing is one of alternatives, however, the relative clinical advantages of RVOT pacing compared with RVA pacing are currently modest or controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because several studies have demonstrated an association between RVA pacing and an increased risk of heart failure or LV dysfunction, 17–20 alternative pacing sites have been investigated intensively 6,21 . RVOT pacing is one of alternatives, however, the relative clinical advantages of RVOT pacing compared with RVA pacing are currently modest or controversial.…”
Section: Discussionmentioning
confidence: 99%
“…RVOT pacing is one of alternatives, however, the relative clinical advantages of RVOT pacing compared with RVA pacing are currently modest or controversial. This is partly due to the tolerance to RVA pacing in patients with healthy or preserved LV systolic function or preserved intrinsic AV conduction such as those with sinus node dysfunction 6,21,22 . Several ongoing clinical trials are therefore underway to further clarify the effects of selective site pacing 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Постоянная электрокардиостимуляция (ЭКС) -единственный метод лечения необратимой симптом-ной брадикардии. Верхушка правого желудочка (ВПЖ) является наиболее часто используемой областью для стимуляции желудочков, так как позиционировать электрод в эту область технически просто, кроме того, обеспечивается хорошая стабильность положения и пороги стимуляции в ближайшие и отдаленные сроки после операции [1]. Однако получены данные, сви-детельствующие о неблагоприятных эффектах сти-муляции из ВПЖ, особенно в отдаленные сроки пос-ле операции [2][3][4].…”
unclassified
“…Однако получены данные, сви-детельствующие о неблагоприятных эффектах сти-муляции из ВПЖ, особенно в отдаленные сроки пос-ле операции [2][3][4]. В ряде работ было показано, что стимуляция межжелудочковой перегородки (МЖП) в ближайшие и отдаленные сроки имеет целый ряд преимуществ и в то же время не хуже по стабильнос-ти и эффективности в сравнении с ВПЖ, кроме того, отмечается низкий риск перфорации сердца, стимуля-ции диафрагмального нерва, а электрод легко удаля-ется при необходимости его замены [1]. Несмотря на логичные анатомо-физиологические обоснования при позиционировании электрода в МЖП, данные клини-ческих исследований имеют противоречивые результа-ты [5, 6].…”
unclassified